Taking the First Steps Towards a Multiparty System in the United States - Anderson, John B.; Freeman, Jeffrey L. (Tufts Archival Research Center, 2005)
Volume 21, Issue 1. Winter/Spring The authors relate the history and dynamics of third-party candidates on U.S. presidential elections.